Law and management in sport, in the activities of third sector organizations on the example of the Association of the Scientific Law of Sports Law - Mierzwa, Piotr; Bugajska, Małgorzata; Raniszewski, Szymon; Borek, Dominik; Dróżdż, Mateusz; Tomanek, Mateusz (Journal of Education, Health and Sport, 2023)
In 2016, three universities in Poland established, on the basis of the provisions of the no longer applicable Act of 30 April 2010 on financing science, the first in Poland "Polish scientific network - Research and development work for the dissemination of sports law". On the basis of this project, the next step was to establish a registered association under the name of Towarzystwo Sieci Naukowej Sportowego (Towarzystwo Sieci Naukowej Sportowego), this entity as a unique entity on the sports market is responsible for the entire spectrum of activities in the field of management and law in sport. The article aims to discuss good practices in the activities of third sector organizations on the example of the said association. The work uses the dogmatic-exegetical method of research, thanks to which the wording of the statute and the agreement of the scientific network were quoted. An empirical method was also used, which is related to the experience of some of the authors - members of the said association.